Environmental health problems of a University Town and their implications for health education - Lavin, Angelina A. (1977)
The purpose of the study was to identify the environmental health problems of University Town and their implications for health education. The study employed the normative survey. A personal observation guide and interview checklist were utilized to gather the needed information on the actual home conditions in the Univesity Town and the prevailing health practices of the people. Based on the findings, an improved school health program may be brought to the attention of the university authorities and the members of the community for its implementation and realization.
"May 1977."
Thesis (M.A.T. Health education)--University of the Philippines, Diliman.
Keywords: Universities and colleges -- Environmental aspects -- Philippines -- Catarman (Northern Samar)